Tonsillar tuberculosis with coexisting lymphoma: A case report - Teoh, Li Ping; Tang, Chian Ling; Heng, Pek Ser; Lim, Li Yun (Malaysian Medical Association, 2021)
The co-existence of tuberculosis (TB) and lymphoma share similar presentations and both may masquerade each other leading to diagnostic dilemmas. Herein, we would like to report a case of an elderly man with existing TB in whom failing to respond to treatment led to investigations that unveiled the coexistence of a non-Hodgkin lymphoma. A 71-year-old man presented to our department with a one-month history of odynophagia and left submandibular swelling. He was treated with multiple courses of antibiotics but symptoms not resolving. Physical examination showed enlarged tonsils bilaterally with exudates. There was also a left cervical lymph node enlargement. Biopsy taken from both tonsils and histopathological examination (HPE) showed no malignancy. Biopsy was also sent for a Genexpert test for tuberculosis and the result was positive for Mycobacterium tuberculosis. A fine needle aspiration was taken from the neck mass and the result was non-diagnostic. As the result from the Genexpert test was positive, he was started on anti-TB treatment. After three months of treatment, the tonsils were still hypertrophied and the left neck nodes never resolved. Suspicion was raised and a second biopsy was done with an incisional biopsy taken from the left neck nodes. The tonsils biopsy still showed no malignancy but the HPE from the neck nodes showed diffuse large B-cell lymphoma. Patient was counselled for chemotherapy but refused. He succumbed to the disease three months after refusal of chemotherapy. The co-existence of extrapulmonary tuberculosis and lymphoma is rare, which leads to a diagnostic dilemma especially if one was not known to have underlying lymphoma. Tuberculosis will usually be suspected first due to our endemic nature and in this case, further investigations were only done when the symptoms were not resolving with anti-TB treatment. Therefore, suspicion of both conditions occurring concurrently should arise early if treatment was unsuccessful.